N‐[2‐(4‐benzoyl‐1‐piperazinyl)phenyl]‐2‐(4‐chlorophenoxy) acetamide is a novel inhibitor of resorptive bone loss in mice. Issue 3 (23rd December 2020) - Chen, Zhihao; Cho, Eunjin; Ding, Mina; Seong, Jihyoun; Che, Xiangguo; Lee, Sunwoo; Park, Byung‐Ju; Choi, Je‐Yong; Lee, Tae‐Hoon
Abstract: The dynamic balance between bone formation and bone resorption is vital for the retention of bone mass. The abnormal activation of osteoclasts, unique cells that degrade the bone matrix, may result in many bone diseases such as osteoporosis. Osteoporosis, a bone metabolism disease, occurs when extreme osteoclast‐mediated bone resorption outstrips osteoblast‐related bone synthesis. Therefore, it is of great interest to identify agents that can regulate the activity of osteoclasts and prevent bone loss‐induced bone diseases. In this study, we found that N ‐[2‐(4‐benzoyl‐1‐piperazinyl)phenyl]‐2‐(4‐chlorophenoxy) acetamide (PPOAC‐Bz) exerted a strong inhibitory effect on osteoclastogenesis. PPOAC‐Bz altered the mRNA expressions of several osteoclast‐specific marker genes and blocked the formation of mature osteoclasts, suppressing F‐actin belt formation and bone resorption activity in vitro. In addition, PPOAC‐Bz prevented OVX‐induced bone loss in vivo. These findings highlighted the potential of PPOAC‐Bz as a prospective drug for the treatment of osteolytic disorders.